A Practicable Measurement Strategy for Compliance Checking Number Concentrations of Airborne Nano- and Microscale Fibers - Asmus Meyer-Plath; Daphne Bäger; Nico Dziurowitz; Doris Perseke; Barbara Katrin Simonow; Carmen Thim; Daniela Wenzlaff; Sabine Plitzko (Atmosphere, 2020)
Despite compelling reports on asbestos-like pathogenicity, regulatory bodies have been hesitant to implement fiber number-based exposure limits for biodurable nanoscale fibers. One reason has been the lack of a practicable strategy for assessing airborne fiber number concentrations. Here, a method is proposed, detailed and tested for compliance checking concentrations of airborne nano- and microscale fibers. It relies on Poisson statistical significance testing of the observed versus a predicted number of fibers on filters that have sampled a known volume of aerosol. The prediction is based on the exposure concentration to test. Analogous to the established counting rules for WHO-fibers, which use a phase contrast microscopy-related visibility criterion of 200 nm, the new method also introduces a cut-off diameter, now at 20 nm, which is motivated by toxicological findings on multi-walled carbon nanotubes. This cut-off already reduces the workload by a factor of 400 compared to that necessary for imaging, detecting and counting nanofibers down to 1 nm in diameter. Together with waiving any attempt to absolutely quantify fiber concentrations, a compliance check at the limit-of-detection results in an analytical workload that renders our new approach practicable. The proposed method was applied to compliance checking in 14 very different workplaces that handled or machined nanofiber-containing materials. It achieved detecting violations of the German benchmark exposure level of 10,000 nanofibers per cubic meter.